Exfoliated 2D Antimonene‐Based Structures for Light‐Harvesting Photoactive Layer of Highly Stable Solar Cells. Issue 6 (6th June 2022) - Bat-Erdene, Munkhjargal; Myagmarsereejid, Purevlkham; Bati, Abdulaziz S. R.; Qin, Jiadong; Zhong, Yu Lin; Shapter, Joseph G.; Batmunkh, Munkhbayar
Abstract : From Oxidized 2D Antimonene to Photoactive Sb2 S3 In article number 2200038, Joseph G. Shapter, Munkhbayar Batmunkh, and co‐workers converted surface‐oxidized 2D antimonene sheets to photoactive Sb2 S3 light absorber for highly stable solar cells. Highly crystalline Sb2 S3 thin films with large grain sizes are obtained by subsequent annealing steps in air and then in a glove box. The devices exhibite outstanding operational stabilities including being able to withstand harsh moisture, light exposure and thermal stress.